Peripartum cardiomyopathy and its relationship with preeclampsia - Christina Meilani Susanto; Khanisyah Erza Gumilar (Universitas Airlangga, 2020)
Objectives: To know the characteristic of PPCM in RSUD Dr. Soetomo Hospital Surabaya and to know the relationship between PPCM and PE.Materials and Methods: This was a case control study. Data was obtained from medical record of 2843 patients within 2014-2015, divided into 2 groups, 19 patients with PPCM in a case group, and 2824 patients in control group. The statistical analysis used was Fisher exact test.Results: Peripartum cardiomyopathy patients were older compared to control group (32.21 ± 6.83 y.o vs 29.26 ± 6.45 y.o). The incidence of PPCM in our study was about 1 per 149 live births. Most cases were diagnosed antepartum (52.63%), and about 84.2% PPCM cases were also complicating with preeclampsia. The statistical analysis revealed that there was increase risk of PPCM if the pregnant women complicates PE during pregnancy, with Odds Ratio (OR) 20.679, p<0.05. The most common perinatal outcomes was Small for Gestational Age (SGA) babies (81.8%), whereas case fatality rate (CFR) in maternal was 15.7%.Conclusion: Although diagnosis of PPCM is still an exclusion diagnosis, we have to pay more attention to pregnant women complicating with preeclampsia, since preeclampsia can increase the risk of PPCM.